2008
DOI: 10.1002/jsfa.3386
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of trypsin from sardinelle (Sardinella aurita) viscera

Abstract: BACKGROUND: In Tunisia, sardinelle (Sardinella aurita) catches totalled about 13 300 t in 2002. During processing, solid wastes including heads and viscera are generated, representing about 30% of the original raw material. Viscera, one of the most important by-products of the fishing industry, are recognised as a potential source of digestive enzymes, especially proteases with high activity over a wide range of pH and temperature conditions. This paper describes the purification procedure and some biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…The enzyme preparations used were: alkaline proteases from B. pumilus A1 (Fakhfakh-Zouari et al 2010) and B. mojavensis A21 (Haddar et al 2009), and crude enzyme extract from viscera of sardinelle (S. aurita) (Ben khaled et al 2008). All proteolytic enzymes were prepared in our laboratory.…”
Section: Enzymesmentioning
confidence: 99%
“…The enzyme preparations used were: alkaline proteases from B. pumilus A1 (Fakhfakh-Zouari et al 2010) and B. mojavensis A21 (Haddar et al 2009), and crude enzyme extract from viscera of sardinelle (S. aurita) (Ben khaled et al 2008). All proteolytic enzymes were prepared in our laboratory.…”
Section: Enzymesmentioning
confidence: 99%
“…However, the data reported by other authors were higher than the values achieved in our study, demonstrating that the trypsin from E. anchoita viscera has a superior affinity for BAPNA. The catalytic efficiency (k cat /K m ) of E. anchoita trypsin by-products, 2.11/s mM was close to that of trypsins from the digestive tract of anchovy E. encrasicholus , sardinella (Sardinella aurita ) (Khaled et al, 2008) and the pancreas of small-spotted catshark (Scyliorhinus canicula ) (Blanco et al, 2014), using the same substrate. Trypsin (EC 3.4.21.4) is a member of the serine proteinase family that specifically hydrolyzes proteins and peptides at the carboxyl side of arginine and lysine residues constituting important roles in biological processes (Cao et al, 2000).…”
Section: Kinetic Studymentioning
confidence: 62%
“…These results are in agreement with the increment obtained by Blanco and coworkers (2014) in the pancreas of small-spotted catshark. Other studies described an opposite effect on trypsins isolated from the intestines of sardinella (Khaled et al, 2008) and of triggerfish (Jellouli et al, 2009). Enzymes that resist the denaturation ability of SDS have been reported earlier (Rao et al, 1989).…”
Section: Effect Of Metallo-protease Inhibitor and Surfactant On Trypsmentioning
confidence: 92%
“…In resemblance with the results of our study, Bougatef et al (2007) asserted that the trypsin from the viscera of sardine at 40 and 50°C remained significantly active even after 250 min of incubation. In addition, Castillo-Yanez et al (2005), Shi et al (2007) and Khaled et al (2008) reported that good thermal stability was observed in fish trypsins incubated at 40°C for 15-45 min, while the enzyme lost all its activity when heated at 60°C for 15 min. The trypsin from hoki fish (Shi et al, 2007) and Sardinella viscera (Khaled et al, 2008) were found to be inactive when heated at 60°C for 30 min.…”
Section: Effect Of Temperature On Activity and Stabilitymentioning
confidence: 99%
“…fishing industry, are recognized as potential source of digestive enzymes, especially proteases with high activity over a wide range of pH and temperature conditions (Castillo-Yanez et al, 2006;Klomklao et al, 2006a;Bougatef et al, 2007;Khaled et al, 2008). Proteases constitute the most important group of industrial enzymes used in the world today (Bougatef et al, 2007;El-Beltagy et al, 2004;Souza et al, 2007), accounting for about 50% of the total industrial enzyme market (Bougatef et al, 2007;Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%